Rotator Cuff Repair Technique With Transosseous Knotless Anchor System - Murphy, Michael M. (Arthrosc Tech, 2018)
Various surgical techniques exist for rotator cuff repair that provide a suitable environment for tendon–bone healing. Arthroscopic recreation of transosseous repairs, which had previously been performed by open or miniopen techniques, can now be performed; however, arthroscopic, transosseous passage of suture material can be challenging technically. There are potential biologic and cost-saving advantages of arthroscopic transosseous rotator cuff repair that make an efficient and reproducible technique desirable for arthroscopists. The technique for arthroscopic transosseous rotator cuff repair using a knotless anchor-based system is demonstrated in the current Technical Note. Potential advantages of this construct include excellent biomechanics, enhanced footprint vascularization, and utility in poor bone quality while using minimal anchor numbers. Further studies will be needed to elucidate healing rates and clinical outcomes.